A single-center retrospective study of ectopic lymphoid tissues in idiopathic membranous nephropathy: clinical pathological characteristics and prognostic value - Jing Zhang; Siyu Chen; Haiying Zheng; Siyi Rao; Yuanyuan Lin; Jianxin Wan; Yi Chen (PeerJ)
Background In recent years, ectopic lymphoid tissue (ELT) has been increasingly confirmed as a new biomarker for kidney injury or inflammation. However, there is insufficient research on the relationship between ELT grading and the progression of idiopathic membranous nephropathy (IMN). Methods A total of 147 patients with biopsy-proven IMN in our institution from March 2020 to June 2022 were classified into five grades based on the different distribution of lymphocyte subsets in renal tissue (G0: no B cells or T cells, G1: scattered B and T cells, G2: clustered B and T cells, G3: an aggregation region of B and T cells without a central network, G4: highly organized and formed zones of B and T cells with a central network of follicular dendritic cells and scattered macrophages), and were further divided into low-grade group (G0+G1), intermediate-grade group (G2) and high-grade group (G3+G4). The clinicopathological data, induction treatment response and prognosis among the three groups were analyzed and compared retrospectively. Results As the grading of ectopic lymphoid tissues increased, patients were older, with a higher prevalence of hypertension, a higher 24-h urinary protein level, lower baseline hemoglobin and estimated glomerular filtration rate (eGFR) levels, and more severe renal pathological damage. Logistic regression analysis showed that after 6 months of induction treatment, patients in the high-grade group were more likely to be in non-remission than those in the low-grade group (odds ratios [ORs] of the three adjusted models were 4.310, 4.239, and 5.088, respectively, P-values were 0.005, 0.006, and 0.001, respectively). Kaplan-Meier survival analysis indicated that patients in the intermediate- and high-grade groups had significantly lower renal cumulative survival rate than those in the low-grade group (P = 0.025). Univariate Cox analysis showed that the risk of adverse renal outcome was 3.662 times higher in the intermediate- and high-grade groups than in the low-grade group (95% confidence interval [CI] [1.078–12.435]; P = 0.037). Multivariate Cox analysis revealed that failure of remission at the first 6 months (hazard ratio [HR] = 5.769; 95% CI [1.854–17.950]; P = 0.002) remained an independent risk factor for poor renal outcome in patients with IMN. Conclusions Grading of renal ectopic lymphoid tissues correlates with disease activity and severity in IMN patients and can be used as an indicator to assess the risk of IMN progression.